NEOINDUSTRIALIZATION AS THE NEW TECHNOTRONIC ECONOMY (BY EXAMPLE OF INTRODUCING ROBOTS TO THE US INDUSTRY) - SERGEY ALEKSANDROVICH Tolkachev; ALEKSANDR DMITRIEVICH Kulakov (Мир новой экономики)
The article considers the concept evolution of „new economy”. It is shown that the approach to this phenomenon prevailing in 1990-2000-ies was based on outdated notions of a purely post-industrial content of the new economy. The global financial crisis of 2008-2009 and subsequent depression of the world economy have deprived us of objective view of contrasting ideas about the new economy as the only post-industrial phenomenon and the „old” economy, concentrated in the sphere of material production. Development of the neoindustrialization processes in the US and Western Europe since 2010 has been infusing the term „new economy” with a new meaning. Now it can be identified with technotronic society, understood as a stage of industrial development, when the machines connectedto the information network can carry out not only physical but also administrative operations instead of a human. The article singles out three areas of technological neoindustrialization: Internet industry, additive manufacturing and robotizing of the industry. Considered are the dynamics and economic motives of proliferation of robots in the US industry. The socio-economic impact of robotics is assessed.